Determinant Factors of Stunting in West Pasaman District, West Sumatera Indonesia - Sari Arlinda; Muchsin Riviwanto; Burhan Muslim; Awalia Gusti; Defriani Dwi Yanti (Universitas Airlangga, 2022)
Introduction: The age group that is susceptible to disease and must get balanced nutrition to avoid stunting is the age group of infants under five years old (toddlers). Toddlers with stunting are caused by many factors, including parenting patterns, health services that can be reached by toddlers, environmental conditions where toddlers live, food consumption as food security for toddlers. The purpose of this research was to know the determinants of stunting in The West Pasaman Regency. Methods: The design of this study was a cross-sectional survey by interviewing 1,156 respondents in West Pasaman Regency which were selected using a simple randomized method. A structured questionnaire that has passed validity and reliability tests was used to collect data. Generalized Structural Equation Modeling was used to determine these determinants. Results and Discussion: The study showed that 30.8% of children under five years old in West Pasaman were stunted with the disease being diarrhea, which was 18.8%. Most of the children under five live in families with a low socioeconomic level, namely 53.9%, with a low education of 58.2%. The results of the re-specification of the model show that the variable that has the greatest indirect influence on the incidence of stunting is the diet variable (path coefficient = 0.90) compared to parenting and environment. Conclusion: Infectious diseases are a direct cause of stunting in toddlers. Parenting behavior factors, eating behavior factors, and environmental factors are indirect causes, but these factors play a very important role in causing stunting in toddlers. Preventive activities are needed, such as counseling for child growth and development, formation of caring for neighbors, a social gathering for nutritious food and pre-marital counseling which discusses parenting, eating patterns, and a sanitary environment